Relationship Between Work Position and Non-Specific Low Back Pain Incidence in Farmer Groups - Ulul Azmi, Farisa; Riska Risty Wardhani; Mustiko, Prihantoro Larasati (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Farmers are someone who spends a lot of time in the field to plant, fertilize and harvest. During the process of planting, farmers tend to be in a bent position for a long time. Low back pain is one of the complaints that can reduce human productivity. Low back pain does not recognize gender, age, or social status. Non-specific low back pain results in pain, muscle spasms, and muscle imbalance, so the stability of the abdominal and lower back muscles decreases, limited lumbar mobility, changes in posture and results in disability in sufferers of non-specific low back pain. The students aim to determine whether there is a correlation between working posture and the incidence of non-specific low back pain in farmers. Methods: The research method used by sampling using total sampling, the dependent variable was the work position and the independent variable in the researcher's research was non-specific low back pain. Results: Sig value. (2-sided) in the chi-square test is 0.018. Because the sig value (2-sided) is 0.018<0.05, then based on the decision-making above, it can be concluded that Ho is rejected Ha is accepted. This means that there is a relationship between working posture and non-specific low back pain in farmer groups. Conclusion: There is a correlation between working posture and the incidence of non-specific low back pain in farmers. Future researchers are expected to add or examine further related postures while working on workers and increase the number of respondents to be more relevant in the coming years